The Correlation among Students’ Reading Interest, Reading Comprehension, and Their Intralingual Translation Achievement - Despita Despita (Fakultas Keguruan dan Ilmu Pendidikan (FKIP), Universitas Lancang Kuning, 2020)
Enthusiasm support a vital role in reading comprehension achievement of upper level readers, Reading interest is vital that one may encourage and maintain their interest of reading. Intralingual translation is defined as “rewording” and as an interpretation of verbal signs by means of other signs of the same language. This research is a quantitative research which has the purpose to find out whether or not there was significant correlation among students’ reading interest, reading comprehension, and their intralingual translation achievement. Furthermore, the population of the research is the second semester students of STIA SATYA NEGARA Palembang consisting of 120 students, from the population, 42 students were represented as the sample which was taken through simple random sampling technique. The instruments used were questionnaire for reading interest, multiple choice test for reading comprehension, and written test for intralingual translation. After having the result, then the data were analyzed by using multiple correlation in SPSS 20 Program for Windows. From the result of the data analysis shows that Ryx1x2 = 0.655 at the significance level of 0.05, and for the criteria of significant test is gotten Fcount (37.037) > Ftable (4.08). So, the result of hypothesis test shows that there is significant correlation among students’ reading interest, reading comprehension, and their intralingual translation achievement. It can be concluded that if students have high interest in reading, so they have good ability in comprehending text.